Photo‐Excited Nickel‐Catalyzed Silyl‐Radical‐Mediated Direct Activation of Carbamoyl Chlorides To Access (Hetero)aryl Carbamides. (30th September 2022) - Maiti, Sudip; Roy, Sayan; Ghosh, Pintu; Kasera, Aashi; Maiti, Debabrata
Abstract: Amide bonds connect the amino acids in proteins and exist as a prevalent structural motif in biomolecules. Herein, we have exploited the concept of cross‐electrophile coupling by merging the photo‐redox and transition‐metal catalysis to construct carbamides from superabundant (hetero)aryl halides along with commercially feasible carbamoyl chlorides. The success of this method relies on the prior formation of Ni II ‐aryl halide intermediates, which involves in a photoexcited Ni‐halide homolysis event by energy transfer from aryl bromide and single‐electron transfer from aryl chloride to assist generation of the vital carbamoyl radical. The breadth of application of this technique is demonstrated both in inter‐ as well as intramolecular routes for the synthesis of a plethora of (hetero)aryl carbamides with diverse functionalities, and biologically important benzolactams. Abstract : Photoexcited nickel catalysis enabled silyl‐radical‐mediated activation of carbamoyl chlorides. This process provides an operationally simple and widely applicable amidation reaction of a plethora of aryl and heteroaryl halides. Mechanistic understanding suggests that the reaction involves an energy‐transfer mechanism for aryl bromide; while a single‐electron‐transfer mechanism is operating for aryl chlorides.